STUDI AWAL RANCANG BANGUN COLORIMETER MENGGUNAKAN SENSOR OPT101 BERBASIS SISTEM ANDROID DENGAN DISPLAY SMARTPHONE - Habibi Putra; Yulkifli Yulkifli (Komunikasi Fisika Indonesia, 2019)
Colorimeter is a color measuring device that is a tool that can distinguish colors based on the value of the output produced. In this study a colorimeter device was made using the OPT101 sensor, an analog sensor based light detector. OPT101 sensor has characteristics if the intensity of light received is getting brighter, the greater the sensor output value and vice versa. Because of the characteristics of the sensor like that, this sensor can be used as a measuring instrument to determine the concentration of a food coloring agent. This study aims to look at investigating the relationship between the concentration value of a dye solution to the OPT101 sensor response value contained in the colorimeter tool. The dyes used are red (metile red) and blue (brilliant blue) with 10 different variations of concentration, with a range of 0.01% -0.1%. After the measurement experiments were carried out on the sample, the results obtained were almost the same as the theory, namely the relationship between the concentration value was inversely proportional to the value of the sensor output. The inverse relationship means that the more concentrated a dye solution is, the more the light intensity penetrates the substance or dims. So that the OPT101 sensor detects a dimmer light source, the sensor output value gets smaller, because the relationship of the sensor output value is directly proportional to the intensity of the received light. Based on the measurements that have been made, the results of sensor response values are obtained for the red sample with a range of data from 276,698 decreasing to 240,762, while for the blue sample from the range 9,828 it decreases to 8.75. The value for the blue sample is much smaller because the blue sample is much thicker than the red sample.